An enhanced cAMP pathway is responsible for the colonic hyper-secretory response to 5-HT in acute stress rats - Li, Y; Li, L. S; Zhang, X. L; Zhang, Y; Xu, J. D; Zhu, J. X (Physiological research, 2015)
5-hydroxytryptamine (5-HT) is involved in the stress-induced alteration of colonic functions, specifically motility and secretion, but its precise mechanisms of regulation remain unclear. In the present study, we have investigated the effects of 5-HT on rat colonic mucosal secretion after acute water immersion restraint stress, as well as the underlying mechanism of this phenomenon, using short circuit current recording (I(SC)), real-time polymerase chain reaction, Western blot analysis, and enzyme-linked immunosorbance assays. After 2 h of water immersion restraint stress, the baseline I(SC) and 5-HT-induced I(SC) responses of the colonic mucosa were significantly increased. Pretreatment with selective 5-HT(4) receptor antagonist, SB204070, inhibited the 5-HT-induced colonic I(SC) response by 96 % in normal rats and 91.2 % in acute-stress rats. However, pretreatment with the selective antagonist of 5-HT(3) receptor, MDL72222 or Y-25130, had no obvious effect on 5-HT-induced I(SC) responses under either set of conditions. Total protein expression of both the mucosal 5-HT(3) receptors and the 5-HT(4) receptors underwent no significant changes following acute stress. Both colonic basal cAMP levels and foskolin-induced I(SC) responses were significantly enhanced in acute stress rats. 5-HT significantly enhanced the intracellular cAMP level via 5-HT(4) receptors in the colonic mucosa from both control and stressed animals, and 5-HT-induced cAMP increase in stressed rats was not more than that in control rats. Taken together, the present results indicate that acute water immersion restraint stress enhances colonic secretory responses to 5-HT in rats, a process in which increased cellular cAMP accumulation is involved.
Keywords: Animals; Intestinal Mucosa; kolon; AMP cyklický; Immersion; Up-Regulation; psychický stres; ponoření; Serotonin; Colon; serotonin; upregulace; signální transdukce; Signal Transduction; Rats, Sprague-Dawley; Cyclic AMP; Male; potkani Sprague-Dawley; Stress, Psychological; krysa rodu Rattus; zvířata; mužské pohlaví; Rats; střevní sliznice